Leprosy in skulls from the Paris Catacombs - Patrícia D. Deps; Simon M. Collin; Sylvie Robin; Philippe Charlier (Annals of Human Biology, 2020)
Background: The Paris Catacombs contain the remains of approximately 6 million people dating back to the 15th century, when leprosy was endemic in France. Aims: The aim of this palaeopathological study was to identify the presence of leprosy in skulls from the Paris Catacombs. Subjects and methods: Macroscopic examination of skulls in situ for bone changes secondary to oronasal soft tissue infection by leprosy. Skulls were categorised as having “probable” signs of leprosy if they had an enlarged nasal (pyriform) aperture, resorption of the anterior nasal spine, and resorption of the alveolar processes of maxilla, and as having “possible” signs of leprosy if they met one of these three criteria. Results: Skulls from 123 sections within the Catacombs (approximately 1500 remains in total) were triaged, with 367 skulls identified as suitable for examination. Of these, 74 had central facial bone alterations/abnormalities and underwent detailed examination, yielding 0.5% (2/367) classified as having probable, and 5.7% (21/367) possible signs of leprosy. Conclusions: The proportion of skulls with probable signs of leprosy gives an approximate estimate (0.5%) for the prevalence of this disease in the population of Paris (or districts of Paris) during the 15–18th centuries.